Analisa Gangguan Hubung Singkat pada Sistem Tenaga Listrik di Pertamina EP-Central Processing Plant Area Gundih Menggunakan Software ETAP 12.6 - Ernia, Ana Dwi, Agus Supardi, S.T., M.T (2017)
Electricity generated from the power plant which is then transmitted through the transmission to the distribution network and the user to be used in everyday life. This distribution process is not free from disruptions arising from material factor/conductor types and distance factor. Disorders that usually arises in the process of distribution is a short circuit. Short circuit consists of four types, there are 3-phase short circuit, single phase to ground short circuit, phase to phase short circuit, and two-phase to ground short circuit. Short circuit analysis performed on the electric power in the Pertamina EP-Central Processing Plant Area Gundih. Short circuit can be analyzed using simulation methods and calculations manually. In the analysis of short circuit, the analysis aims to determine how much the short-circuit current that occurs at different bus each in turn. The method used is started by the collection of data and information, create a single line diagram in ETAP 12.6, checks the load flow simulation, simulating short circuit analysis, perform manual calculations, making comparisons and conclusions. The conclusion of the analysis is there are difference value of short circuit fault current before and after passing through transformer. Bus-connected right after the transformer and bus-connected load have the same short circuit current value at which the bus 239 to MCC 4111A with large current 40.571 KA 3 phase fault, 42.323 KA single phase to ground fault. Calculation of short circuit current can be used to determine: safety capacity, type of relay, load size, and the installation of the appropriate relay.